Farmer groups enterprises and the marketing of staple food commodities in Africa - Coulter, Jonathan (International Food Policy Research Institute, 2007)
There are some apparently successful cases of collective marketing with staple food commodities (grains and root crops), but these are less common than cases involving higher value agricultural products. These can be attributed to the benefit/cost ratio to participants being generally higher for collective marketing of the higher-value crops. Some of the costs are ‘hidden’, in the sense that they are borne by individuals in time spent in attending meetings, and not shown in the financial statements of the enterprises concerned. Examining a series of cases, the paper advocates an approach to the marketing of staples which involves analyzing the value chain and identifying those activities which on the one hand, best lend themselves to individual initiative, and those where on the other hand, group approaches are more likely to prosper. Dual purpose food marketing involving village storage in anticipation of both external market opportunities and local lean season shortages usually falls into the former category. Collective initiatives have a higher probability of success when they complement agricultural intensification and involve bulking substantial quantities of produce for quality-conscious commercial buyers. Prospects for successful collective marketing are moreover greater where there is a history of collective endeavor, where focused on simple activities like bulking and distribution of inputs, where primary groups are small and homogenous in terms of interests and objectives, where they can establish lasting relationships with strong trade counterparties, where supported by effective training (especially re attitudes, numeracy, and business skills), where they can access effectively managed storage and inventory credit services, and where there is framework of law enforcement. The immediate poverty alleviation and programmatic priorities of funding agencies often undermine the effectiveness of promotional activities in support of collective marketing. This problem may be addressed by instituting systems of independent review and peer review processes, and involving open discussion of pros and cons of individual and collective approaches.